The Impact of Fintech-Based Digital Payments and Saving Intention on Consumptive Behavior: the Moderating Role of Financial Literacy Among Economics Students - Sofia Asyriana Br. P; Gadis Alfiya Kadrun Nada (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study investigates the influence of fintech-based digital payment usage and saving intention on the consumptive behavior of students at the Faculty of Economics, Universitas 17 Agustus 1945 Banyuwangi. It also examines whether financial literacy strengthens or weakens the relationship between these variables and consumptive behavior. A quantitative explanatory research design was employed, with primary data collected through questionnaires distributed to undergraduate students from the 2022–2025 cohorts. Using a purposive sampling technique, 99 valid responses were obtained for analysis. The proposed research model was analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The findings reveal that the use of fintech-based digital payment services does not significantly influence students’ consumptive behavior. Likewise, saving intention does not show a direct and significant effect on consumptive behavior. Furthermore, financial literacy does not significantly moderate the relationship between fintech-based digital payment usage and consumptive behavior. In contrast, financial literacy significantly strengthens the relationship between saving intention and consumptive behavior. These results suggest that students primarily use digital payment services as a practical transaction method rather than as a factor that encourages excessive consumption. Moreover, a higher level of financial literacy appears to reinforce the positive influence of saving intention in reducing consumptive behavior. The study highlights the importance of improving financial literacy as an essential strategy for promoting responsible financial decision-making among university students.